Pengenalan Rambu Lalu Lintas sebagai Sarana Pembelajaran bagi Anak Sekolah Dasar melalui Media Diorama - nani risna wati; Teguh Prayitno; Nindy Purna Palupi (Universitas Muria Kudus, 2025)
This study investigates the effectiveness of diorama media in introducing traffic signs to elementary school students through a qualitative descriptive approach. Twenty-five fourth graders from an elementary school in Bandung were observed through participatory observation, semi-structured interviews, and documentation. Data were analyzed using the Miles and Huberman model. Results show that diorama-based learning increased students’ recognition of traffic signs from 35% to 85% and fostered active participation and collaboration. Students better understood the meaning and context of traffic symbols while demonstrating improved traffic discipline. The use of dioramas made abstract concepts tangible, aligning with Constructivist Learning Theory and Dual Coding Theory. This approach proved effective in enhancing conceptual understanding, engagement, and value formation. It is recommended that teachers receive training in diorama-based learning and explore augmented reality integration for future applications